Assessment Of The Effectiveness Of Methods Used In The Teaching And Learning Of Mathematics In Narok North Sub County - Ng’ethe, Mary M.; Shinali, Maryconsolata; Peter, Koech (Educational Research International, 2018)
The purpose of this study was to assess the effectiveness of techniques used in the teaching and learning of mathematics in Narok North Sub County. Many teaching and learning techniques have been adopted by different pre-schools in Narok North Sub County. This study was carried out to: describe the techniques used by teachers of mathematics in selected pre-schools and assess the effectiveness of the techniques used by the teachers in the teaching of mathematics. The study was based on Piaget's cognitive development theory. The central concern of this theory is the relationship between child cognitive development and teaching of concepts. The study adopted descriptive survey design. The study focused on both private and public pre-schools. Systematic random sampling was used to select 15 out of 54 pre-schools. The study collected data using observation schedules and questionnaires. The data collected was analyzed qualitatively and quantitatively with the help of SPSS version 20 through the use of numbers, descriptive statistics and was presented in frequency tables, percentages, and pie-charts. The findings of this study will be useful to policy makers in identifying areas of concern in Early Childhood Education and address them in the best interest of the child. It also will assist curriculum developers to identify the loopholes that are present in the teaching of Mathematics and finally it also will assist pre-school teachers to come up with the best methods that are suitable to be used in teaching pre-school children in the county.
Keywords: Techniques; Early Childhood Education; pre-unit; pre-school